Language Whistling: a Comparison between Silbo and Solresol / Lingva fajfado: komparo inter Silbo kaj Solresol (InKoj. Philosophy & Artificial Languages, New series, 2011)
Abstract The idea that natural languages can be whistled, in  order to be more perfect than ordinary, spoken ones, has always been  fascinating. This short communication presents a comparison between  one of the most important actual whistled languages in use, i.e.,  Silbo, and one of the most important a-priori languages  proposed in the past, i.e., Solresol. A series of theoretical  reflections about the very concept of language are then offered.Resumo La ideo, ke ekzistas homaj lingvoj fajfitaj, kiuj  estas pli perfektaj ol la normalaj, parolitaj, ĉiam enhavis  propran ĉarmon. Ĉi tiu mallonga artikolo prezentas komparon inter unuela nune uzita fajfa lingvo, nome Silbo, kaj unuela plej  grava apriora lingvo de la pasinteco, nome Solresol. Serio da teoriaj konsideroj estas donitaj poste